2020
DOI: 10.1002/ygh2.418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on surveillance of hepatocellular carcinoma: A study in patients with chronic hepatitis C after sustained virologic response

Abstract: Background The current coronavirus disease 2019 (COVID‐19) pandemic has strongly influenced many aspects of the medical care, including cancer surveillance. Aims We investigated how the COVID‐19 pandemic influenced surveillance for hepatocellular carcinoma (HCC), focusing on patients with hepatitis C virus infection who were receiving surveillance for HCC after sustained virologic response (SVR) in Japan. Methods Patients who achieved SVR between 1995 and 2017 and continued receiving surveillance were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In patients with hepatitis C virus who were following up for HCC, there was significant reduction in their scheduled visits, i.e. , by before 75%, 63.0%, and 49.1% in March to May 2020, respectively, compared with 97% before February 2020[ 132 ]. Surgical interventions for HCC have significantly declined or stopped across many centers in the world due to increased risk of blood transfusion, ICU stay, prolonged hospitalization and developing COVID-19 after surgery[ 133 ].…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…In patients with hepatitis C virus who were following up for HCC, there was significant reduction in their scheduled visits, i.e. , by before 75%, 63.0%, and 49.1% in March to May 2020, respectively, compared with 97% before February 2020[ 132 ]. Surgical interventions for HCC have significantly declined or stopped across many centers in the world due to increased risk of blood transfusion, ICU stay, prolonged hospitalization and developing COVID-19 after surgery[ 133 ].…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…This is particularly true for HCC: despite the task of guaranteeing the safety of our patients, facing a new infection with increased mortality risk in patients with cirrhosis, we needed to maintain treatments of HCC and in the adequate timeframe 2‐4 . While studies had shown how deep the pandemic has changed the management of HCC with respect to surveillance, diagnosis and treatment, none has evaluated the effectiveness of the measures taken to cope with COVID‐19 1,5‐7 . To evaluate the impact of new measures deployed for HCC management during the pandemic, we compared the efficiency and clinical quality key performance indicators (KPI) generated from 2020 to 2019.…”
Section: Introductionmentioning
confidence: 99%
“…DAAs therapy resulted in significantly higher sustained virologic response (SVR) rates in over 95% of the cases, in all HCV genotypes (7). However, successful antiviral therapy does not completely obliterate the risk of HCC occurrence; therefore, it is highly essential that HCC screening never stops in these patients (8,9). Moreover, except for increasing the likelihood of hepatic malignancy, HCV chronic infection is responsible for a large variety of extrahepatic manifestations (including metabolic disorders, extrahepatic malignancies, autoimmune or inflammatory disorders), and therefore, is considered a systemic disease, rather than just a liver condition (4,(10)(11)(12)(13).…”
mentioning
confidence: 99%